Liquid Crystalline Properties of Synovial Fluid - Szwajczak, E.; Kucaba-Piętal, A.; Telega, J.J. (Engineering Transactions, 2001)
The main aim of this paper is to discuss the liquid crystalline concept of synovial fluid. This new concept was proposed by KUPCHINOV [30] and was next developed in [31, 32, 58]. According to these papers, the crystalline structure of synovia ensures very low friction coefficient in human (and animal) joints. Experimental data in favour of crystalline structure of synovia have been discussed. Mathematical model of such fluid, based on ERINGEN'S theory [14, 15], has been advanced.